Synthesis and electrochemistry of LiNi0.6Fe 0.3-xMg0.1+Xo2 (X = 0, 0.5 And 1.0) materials for lithium-Ion batteries - Arof, Abdul Kariem; Sethuprakhash, V.; Basirun, Wan Jefrey (Springer Verlag (Germany), 2005)
Lithium nickel oxide cathodes doped with Fe and Mg was synthesized by the solid state reaction method at 800°C. Structural investigation of these materials was performed using XRD and EDAX. The electrochemical behavior was studied using galvanostatic charge/discharge in order to investigate the performance of LiNi0.6Fe0.3Mg0.1O2, LiNi0.6Fe0.25Mg0.15O2 and LiNi 0.6Fe0.2Mg0.2O2 materials. It is shown that LiNi0.6Fe0.3Mg0.1O2 produced about 96 m Ah/g of discharge capacity.